(untitled) (Bangladesh Pharmaceutical Journal, 2020)
Fenofibrate, a water insoluble drug was used to prepare matrix tablet with four different viscosity grades of Hydroxypropyl Methylcellulose (HPMC) which were Methocel K4M CR, Methocel K15M CR, Methocel K100M CR and Methocel K100LV CR. The concentration of those excipients was 5, 10, 20, and 40% (w/w), respectively. The content of drug in a fixed quantity of powder in every formulation was ranged between 96.47 to 104.78 %. The dissolution study was done by using USP dissolution apparatus II. The kinetics of release was analyzed by using zero-order, first order, Korsmeyer-Peppas, Higuchi and Hixon-crowell equations to explain the drug release mechanism from the matrix tablets. In-vitro dissolution profile of matrix tablets were dependent upon the HPMC concentration and dissolution was rapid for tablets containing lower polymer proportion i.e. 5,10, and 20% Percentage (w/w) HPMC than those containing 40% (w/w) HPMC. Bangladesh Pharmaceutical Journal 23(1): 10-16, 2020